2007
DOI: 10.1017/s1743921308016888
|View full text |Cite
|
Sign up to set email alerts
|

Type I planetary migration in a self-gravitating disk

Abstract: We investigate the tidal interaction between a low-mass planet and a selfgravitating protoplanetary disk, by means of two-dimensional hydrodynamic simulations. We first show that considering a planet freely migrating in a disk without self-gravity leads to a significant overestimate of the migration rate. The overestimate can reach a factor of two for a disk having three times the surface density of the minimum mass solar nebula. Unbiased drift rates may be obtained only by considering a planet and a disk orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, Type-I migration is valid only in isothermal disks. Instead, it has recently been shown that migration can be outwards in disks that transport and dissipate heat inefficiently [43][44][45] .…”
Section: Defining a Plausible Evolution Scenario For The Giant Planetsmentioning
confidence: 99%
“…However, Type-I migration is valid only in isothermal disks. Instead, it has recently been shown that migration can be outwards in disks that transport and dissipate heat inefficiently [43][44][45] .…”
Section: Defining a Plausible Evolution Scenario For The Giant Planetsmentioning
confidence: 99%
“…However, since the disk seems to be too massive for a planet to open a gap detectable at the current resolution 34 , observations at higher resolution are needed to search for a gap and check for this scenario. In addition, since it has been suggested that the spiral arms in Elias 2-27 are due to a so-far undetected external companion in the disk plane 11 , it is natural to ask whether the spiral arms in the VLA 1 disk can also be driven by an external companion.…”
mentioning
confidence: 99%
“…( 18) we can infer that the relative mass growth, 1/m(dm/dt), for each object is important. Let us assume we start out with m 1 > m 2 , then we see that this ratio is increasing if the relative growth increases with m, because then the right-hand side in (18) is positive. This is exactly the situation for runaway-growth.…”
Section: Modes Of Growthmentioning
confidence: 98%